2013
DOI: 10.1007/s13197-013-0953-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antidiabetic and inhibitory potential of turmeric (Curcuma longa L) rhizome against cellular and LDL oxidation and angiotensin converting enzyme

Abstract: Turmeric (Curcuma longa L) rhizome extracts were evaluated for their antidiabetic, antihypertensive and antioxidant potentials. α-Glucosidase (0.4 μg/mL) and α-amylase (0.4 μg/mL) inhibitory potential of turmeric ethyl acetate extract was significantly higher than those of the reference drug acarbose (17.1 μg/mL and 290.6 μg/mL respectively). Protein glycation inhibitory potential of ethyl acetate extract was 800 times higher than that of ascorbic acid. High potential of ethyl acetate extract to scavenge free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…3) Índice de refracción. 4) Grados Brix: extracto seco disuelto en el solvente a 20,1 °C Extracto crudo 0,8144 ± 0,0005 (5) 160,31 ± 0,0069 1,3411 ± 0,0001 (5) 5,7167 ± 0,0289 (5) 5,9 ± 0,01 Reportes de investigaciones como Lekshmi et al (16) , sobre capacidad de captación de radicales de extractos de rizoma de cúrcuma en metanol por el método de DPPH, reportan valores de 53,7 ± 0,82 µg/mL y para la estándar curcumina IC50 es 6,90 ± 0,43 µg/mL. Comparados con nuestros resultados en etanol a 96%, los valores son IC50 6,89 ± 0,002 µg/mL para estándar curcumina y para extracto en etanol es 17,07 ± 0.004 µg/mL.…”
Section: Tabla 1 Resultados De Los Parámetros Fisicoquímicos Del Extunclassified
“…3) Índice de refracción. 4) Grados Brix: extracto seco disuelto en el solvente a 20,1 °C Extracto crudo 0,8144 ± 0,0005 (5) 160,31 ± 0,0069 1,3411 ± 0,0001 (5) 5,7167 ± 0,0289 (5) 5,9 ± 0,01 Reportes de investigaciones como Lekshmi et al (16) , sobre capacidad de captación de radicales de extractos de rizoma de cúrcuma en metanol por el método de DPPH, reportan valores de 53,7 ± 0,82 µg/mL y para la estándar curcumina IC50 es 6,90 ± 0,43 µg/mL. Comparados con nuestros resultados en etanol a 96%, los valores son IC50 6,89 ± 0,002 µg/mL para estándar curcumina y para extracto en etanol es 17,07 ± 0.004 µg/mL.…”
Section: Tabla 1 Resultados De Los Parámetros Fisicoquímicos Del Extunclassified
“…It has been recognized that the hypoglycemic effect of turmeric is mostly through the inhibition of α‐glucosidase and α‐amylase (Lekshmi, Arimboor, Nisha, Menon, & Raghu, 2014). However, our findings suggest that a decrease of glucose diffusion could also contribute to this biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning to carbohydrase enzymes inhibition, Lekshmi et al (2014) reported that turmeric extracts exert a significant inhibitory, even higher than acarbose. However, none of the supplements that we analyzed exhibited significant inhibition on α ‐amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Both plants Curcuma longa (CL) and Rauvolfia serpentina (RS), were previously reported as antihypertensive herbs (Soni et al, 2016) and possess ACE inhibition potential (Lekshmi et al, 2014;Ranjini et al, 2015). Therefore, in the present study the mixture of CL and RS (CL+RS) was evaluated as green ACE inhibitor to manage the angiotensin-II dependent hypertension in dogs, induced through Goldblatt 2 kidney 1 clip Reno vascular hypertension model (2K1C RVHM).…”
Section: Discussionmentioning
confidence: 99%